Qarakhanid roads to China : a history of Sino-Turkic relations - Duturaeva, Dilnoza (Handbook of Oriental studies. section 8 Uralic & Central Asian studies, 2022)
"Qarakhanid Roads to China reconsiders the diplomacy, trade and geography of transcontinental networks between Central Asia and China from the 10th to the 12th centuries and challenges the concept of "the Silk Road crisis" in the period between the fall of the Tang Dynasty and the rise of the Mongols. Utilizing a broad range of Islamic and Chinese primary sources together with archaeological data, Dilnoza Duturaeva demonstrates the complexity of interaction along the Silk Roads and beyond that, revolutionizes our understanding of the Qarakhanid world and Song-era China's relations with neighboring regions"--